Multibeam bathymetry processed data (Kongsberg EM 122 entire dataset) of RV MARIA S. MERIAN during cruise MSM113 - Luisa Rollwage; Jacob Geersen; Christoph Böttner; Felix Gross; Sebastian Krastel (PANGAEA, 2024)
The bathymetric and backscatter map were generated from EM122 multibeam data collected during RV Maria S. Merian cruise 113 between 07 and 12 January 2023. The data cover the western flank of La Palma island and were collected as part of the Sub:Palma side user project. The aim of the Sub:Palma project was to investigate deformation along the western flank of La Palma, where Cumbre Vieja volcano erupted in late 2021. The bathymetric data were processed using the software QIMERA and included correcting systematic errors (e.g. applying sound velocity profiles that were recorded during the cruise) and manual editing of the data. After manually deleting single beams with the 3D slice editor, the data were gridded to 60 x 60 m. The processed multibeam data were loaded into the software FMGT and a backscatter map (mosaic size 40 m) was created.